2015
DOI: 10.1371/journal.pone.0117115
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sterol Regulatory Element-Binding Protein Gene (sreA) Identified in Penicillium digitatum Is Required for Prochloraz Resistance, Full Virulence and erg11 (cyp51) Regulation

Abstract: Penicillium digitatum is the most destructive postharvest pathogen of citrus fruits, causing fruit decay and economic loss. Additionally, control of the disease is further complicated by the emergence of drug-resistant strains due to the extensive use of triazole antifungal drugs. In this work, an orthologus gene encoding a putative sterol regulatory element-binding protein (SREBP) was identified in the genome of P. digitatum and named sreA. The putative SreA protein contains a conserved domain of unknown func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 56 publications
0
39
2
Order By: Relevance
“…Active SREBP turns on the expression of sterol synthesis enzymes and other oxygen-dependent proteins (Blatzer et al, 2011;Choi et al, 2015). Recently, Liu et al (2015) identified a novel SREBP gene (sreA) that was required for DMI-resistance and Cyp51 expression in Penicillium digitatum. In our study, we also identified a gene encoding SREBP induced along with ergosterol biosynthesis genes in both strains (Table 1), perhaps suggesting that oxygen is limiting and/or ergosterol deficiency is sensed in C. beticola cells upon DMI exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Active SREBP turns on the expression of sterol synthesis enzymes and other oxygen-dependent proteins (Blatzer et al, 2011;Choi et al, 2015). Recently, Liu et al (2015) identified a novel SREBP gene (sreA) that was required for DMI-resistance and Cyp51 expression in Penicillium digitatum. In our study, we also identified a gene encoding SREBP induced along with ergosterol biosynthesis genes in both strains (Table 1), perhaps suggesting that oxygen is limiting and/or ergosterol deficiency is sensed in C. beticola cells upon DMI exposure.…”
Section: Discussionmentioning
confidence: 99%
“…HLH-domain proteins 351 constitute a large family of proteins acting as gene expression regulators(Massari & Murre 352 2000). Some members of this family were shown to boost drug resistance gene expression in 353 human tumors(Cheung 2004;Vandeputte et al 2002) and plant pathogens(Liu et al 2015). 354…”
mentioning
confidence: 99%
“…However, prochloraz can also inhibit activities of other CYP enzymes, including cytochrome P450 c17α‐hydroxylase/17, 20‐lyase (CYP17) and aromatase (CYP19) . In P. digitatum , deletion of sreA , a novel sterol regulatory element‐binding protein gene led to increased susceptibility to prochloraz, and prochloraz‐induced expression of cyp51A and cyp51B in P. digitatum was completely abolished in the ΔsreA strain . Thus, prochloraz could inhibit other CYPs and the induction of FoCYP51 expression by prochloraz might not be its function but a mechanism of resistance.…”
Section: Discussionmentioning
confidence: 99%